2015
DOI: 10.1128/mbio.00354-15
|View full text |Cite
|
Sign up to set email alerts
|

The Legionella Kinase LegK2 Targets the ARP2/3 Complex To Inhibit Actin Nucleation on Phagosomes and Allow Bacterial Evasion of the Late Endocytic Pathway

Abstract: Legionella pneumophila, the etiological agent of legionellosis, replicates within phagocytic cells. Crucial to biogenesis of the replicative vacuole is the Dot/Icm type 4 secretion system, which translocates a large number of effectors into the host cell cytosol. Among them is LegK2, a protein kinase that plays a key role in Legionella infection. Here, we identified the actin nucleator ARP2/3 complex as a target of LegK2. LegK2 phosphorylates the ARPC1B and ARP3 subunits of the ARP2/3 complex. LegK2-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 52 publications
6
74
0
Order By: Relevance
“…Apoptosis and inflammasome inhibition are clearly strategies to sustain the macrophage host for Coxiella's lengthy infectious cycle, with subversion of several vesicular trafficking pathways providing the CCV membrane and nutrients. However, the complex effector pool of Coxiella undoubtedly modulates additional eukaryotic systems for pathogen benefit such as the cytoskeleton [146], ubiquitination [147] and nuclear processes via the activity of an emerging class of effectors known as nucleomodulins [148,149]. Elucidating signal transduction events that trigger effector translocation, the temporal reliance on effector groups during infection and whether effector-effector regulation occurs [150,151], are of much interest to the field.…”
Section: Future Perspectivementioning
confidence: 99%
“…Apoptosis and inflammasome inhibition are clearly strategies to sustain the macrophage host for Coxiella's lengthy infectious cycle, with subversion of several vesicular trafficking pathways providing the CCV membrane and nutrients. However, the complex effector pool of Coxiella undoubtedly modulates additional eukaryotic systems for pathogen benefit such as the cytoskeleton [146], ubiquitination [147] and nuclear processes via the activity of an emerging class of effectors known as nucleomodulins [148,149]. Elucidating signal transduction events that trigger effector translocation, the temporal reliance on effector groups during infection and whether effector-effector regulation occurs [150,151], are of much interest to the field.…”
Section: Future Perspectivementioning
confidence: 99%
“…Studies into the function of bacterial effectors suggested that these pathogenic factors demonstrate unparalleled abilities to manipulate a wide spectrum of host cell's processes including facilitating alterations in cytoskeletal rearrangement (17,18), vesicular trafficking (19,20), signal transduction (21,22) and transcription regulation (23,24). To achieve these effects, effectors are often involved in posttranslational modification (PTM) of specific host proteins.…”
mentioning
confidence: 99%
“…ATM/MKA14 regulatory networks have also been shown to regulate cytoplasmic targets, resulting in extensive cytoskeletal rearrangements (Pines et al, 2011). Acting on these cascades could favor the maturation of Ehrlichia -containing vacuoles, as shown for L. pneumophila which controls vesicle trafficking to escape host defenses and counteract the endocytic pathway (Michard et al, 2015). Finally, some candidate T4Es could affect metabolic proteins, like SYVN1, which acts as an E3 ubiquitin-protein ligase.…”
Section: Discussionmentioning
confidence: 99%